2001
DOI: 10.1557/proc-697-p9.1
|View full text |Cite
|
Sign up to set email alerts
|

Superlubricity and Wearless Sliding in Diamondlike Carbon Films

Abstract: Diamondlike carbon (DLC) films have attracted great interest in recent years mainly because of their unusual optical, electrical, mechanical, and tribological properties. Such properties are currently being exploited for a wide range of engineering applications including magnetic hard disks, gears, sliding and roller bearings, scratch resistant glasses, biomedical implants, etc. Systematic studies on carbon-based materials in our laboratory have led to the development of a new class of amorphous DLC films that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Just like H-free a-C, they exhibit a decrease in friction coefficient in the presence of water vapor [176]. The main difference of UNCD and ta-C from H-DLC must come from the difference in the surface energy and reactivity of the surfaces of these materials [187]. On UNCD, Konicek et al found that, at low normal loads, an RH of as low as 0.5% was sufficient to eliminate the run-in period of high friction and gave ultra-low friction coefficient [188,189].…”
Section: Environmental Effect On Friction and Wear Of Carbon Materialsmentioning
confidence: 99%
“…Just like H-free a-C, they exhibit a decrease in friction coefficient in the presence of water vapor [176]. The main difference of UNCD and ta-C from H-DLC must come from the difference in the surface energy and reactivity of the surfaces of these materials [187]. On UNCD, Konicek et al found that, at low normal loads, an RH of as low as 0.5% was sufficient to eliminate the run-in period of high friction and gave ultra-low friction coefficient [188,189].…”
Section: Environmental Effect On Friction and Wear Of Carbon Materialsmentioning
confidence: 99%
“…Within the range of these studies single crystal diamond surfaces have been extensively employed as models of the more important larger-scale industrial surfaces. Insight gained from these studies has helped the community understand surface energetic processes, including the recent manifestation of super lubricity of hydrogen-covered surfaces [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Fluorination of these surfaces has also been explored in an effort to further reduce the coefficient of friction (COF); in particular it was noted that the significant accumulated negative charge on the surface fluorine atom and its tight surface structure, due to strong lateral interactions, lead to a strong repulsive force between interacting surfaces (larger than when hydrogen terminated) [17]. This decrease in friction between interacting surfaces can have far ranging industrial and environmental importance [5,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The friction coefficients of these films are low in humid test environments but become high in vacuum or inert test chambers. DLC films consisting of mostly sp 3 -bonded carbons are very hard (like diamond), and their tribological behavior is claimed to be similar to that of diamond [23,[39][40][41].…”
Section: Classification Of Dlc Filmsmentioning
confidence: 99%
“…In particular, the friction coefficients of highly hydrogenated (containing ~40 at. % hydrogen) DLCs were reported to be as low as 0.001 in dry nitrogen and/or high vacuum environments [23]. Such superlow friction values are not attainable with hydrogen-free DLC films.…”
Section: Chemical and Structural Nature Of Superlubricious Dlc Filmsmentioning
confidence: 99%